Data envelopment analysis: a comprehensive text with models, applications, references and DEA-solver software - 248716 Cooper, William W. (William Wager), 1914-; Seiford, Lawrence M.; Tone, Kaoru, 1931- (Boston: Kluwer Academic Publishers, 2000)
36